2021
DOI: 10.1088/1755-1315/934/1/012009
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Fermented Rice Bran used as Feed Ingredient on Apparent Digestibility Coefficient of Tilapia (Oreochromis niloticus) Feed

Abstract: This study aimed to investigate the effect of fermented rice bran used as a feed ingredient on the apparent digestibility coefficient (ADC) of tilapia feed. The fermentation process was conducted under aerobic conditions using 2% Aspergillus niger for 24 hours. Moreover, three different types of feed were prepared with 3 replicates and these include treatment A (reference feed), B (unfermented rice bran feed), and C (fermented rice bran feed). These treatments were provided for the tilapia for 30 days. Meanwhi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(8 citation statements)
references
References 13 publications
2
6
0
Order By: Relevance
“…Anwar et al (2020) (2014) who reported that the digestibility of protein and fat in A. niger fermented copra meal-based feed were significantly higher than the unfermented one in milkfish rearing. Putra et al (2021) also obtained the same results, where the A. niger fermented rice bran-based feed had higher dry matter digestibility and energy value (P<0.05) in tilapia compared to the unfermented feed.…”
Section: Discussionsupporting
confidence: 63%
See 4 more Smart Citations
“…Anwar et al (2020) (2014) who reported that the digestibility of protein and fat in A. niger fermented copra meal-based feed were significantly higher than the unfermented one in milkfish rearing. Putra et al (2021) also obtained the same results, where the A. niger fermented rice bran-based feed had higher dry matter digestibility and energy value (P<0.05) in tilapia compared to the unfermented feed.…”
Section: Discussionsupporting
confidence: 63%
“…The temperature range in this study was 28.3-30.3 o C, pH 8.16-8.22, DO 5.2-5.8 and ammonia 0.0048-0.006 ppm. Based on Begum et al (2014), the value of water quality parameters in this study Putra et al (2022) is still within the range of water quality values for tilapia rearing.…”
Section: Feeding and Digestibility Test On Tilapiasupporting
confidence: 61%
See 3 more Smart Citations